(untitled) (Research, Society and Development, 2021)
Introduction: Cadmium is a heavy metal found in the environment that is used industrially; however, it also causes hepato- and nephrotoxic effects. Objective: To evaluate the effect of drinking water pH on the hepato- and nephrotoxicity caused by chronic cadmium poisoning. Material and Methods: We used 90 adult, male Wistar albino rats divided into 6 groups (n = 15): GC5 received a solution of cadmium chloride in drinking water with an acidic pH (pH 5.0); GC7 received a solution of cadmium chloride (400 mg/L) in drinking water with a neutral pH (pH 7.0 water); GC8 received a solution of cadmium chloride in water with an alkaline pH (pH 8.0); GWC5 received drinking water with an acidic pH (pH 5.0); GWC7 received drinking water with a neutral pH (pH 7.0); GWC8 received drinking water with an alkaline pH (pH 8.0). The animals were euthanized 6 months after the start of the experiment. We performed tests for hepatic and renal function and conducted liver and renal histopathology. Results: Water with an acidic pH caused alterations in ALP, ALT and urea in animals exposed to cadmium (P<0.05). In the liver, the majority of animals from the GC7 (57.1%) and GC5 (53.3%) groups showed diffuse microvesicular steatosis, while other groups showed no steatosis (P>0.05). In the kidney, the majority of animals from the GC7 (78.6%) and GWC5 (71.4%) groups showed tubular hydropic degeneration; however, these data were only statistically different from the GWC7 group (P<0.05). Conclusion: Exposure to cadmium in water with an acidic pH led to higher elevations of serum ALP, AST and urea, suggesting that the pH of drinking water influences the hepato- and nephrotoxic effects of this heavy metal.